Pengaruh pelatihan dan kompensasi terhadap kinerja pegawai dengan dorongan sebagai variabel intervening - Fauzi, Rahmad Danial; Sutawidjaya, Ahmad Hidayat; Maria, Maya (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study uses motivation as an intermediary variable to explain how training and pay affect employee performance. This study uses a qualitative approach. The method used is by survey. The type of research used is the study of causality. With a total sample size of 43 participants, this study was carried out in the production division of PT Pertamina Hulu Energi West Madura Offshore's Onshore Receiving Facility (ORF PT PHE WMO). Training and compensation are exogenous variables in this quantitative research method. Motivation serves as a mediating variable and performance is an endogenous variable. With the help of a Likert scale, the factors were measured. The Structural Equation Model Partial Least Square (SEM PLS) technique and SmartPLS 3 software were utilized for data analysis. According to the study's findings, motivation, training, and compensation all had a direct, beneficial, and significant impact on performance. The training and compensation variables and the ability to mediate have a favorable and significant indirect connection on performance.